2020
DOI: 10.12928/pharmaciana.v10i2.16311
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Zingiber cassumunar Roxb rhizome extract on in vitro phagocytic activity and lymphocyte proliferation

Abstract: Zingiber cassumunar Roxb (Bengal ginger) is among the medicinal plants possessing immunomodulatory potentials. It contains curcumin and some volatile compounds that reportedly exhibit immunomodulatory activities. This study set out to examine and determine the effect of ethyl acetate fraction of Z. cassumunar rhizome extract on phagocytic activity of macrophages and lymphocyte proliferation in vitro. Z. cassumunar rhizomes were macerated with 96% ethanol solvent and then fractionated using ethyl acetate. Macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Among the compounds, (E)-4-(3′,4′-dimethoxyphenyl) but-3-en-1-ol has the highest immunostimulant activity (Chairul et al, 2008). Mahfudh et al (2020a) demonstrated the in vitro effect of ethyl acetate extract (25, 50, and 100 μg/ml) of Z. cassumunar rhizomes on lymphocyte proliferation and phagocytic activity of mice macrophages. The extract at 100 μg/ml exhibited the strongest phagocytic activity as measured by phagocytosis index and an increase in active phagocytes.…”
Section: In Vitro Immunomodulating Effects Of Zingiber Cassumunarmentioning
confidence: 98%
“…Among the compounds, (E)-4-(3′,4′-dimethoxyphenyl) but-3-en-1-ol has the highest immunostimulant activity (Chairul et al, 2008). Mahfudh et al (2020a) demonstrated the in vitro effect of ethyl acetate extract (25, 50, and 100 μg/ml) of Z. cassumunar rhizomes on lymphocyte proliferation and phagocytic activity of mice macrophages. The extract at 100 μg/ml exhibited the strongest phagocytic activity as measured by phagocytosis index and an increase in active phagocytes.…”
Section: In Vitro Immunomodulating Effects Of Zingiber Cassumunarmentioning
confidence: 98%